2016
DOI: 10.1038/srep34689
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration, daytime napping, markers of obstructive sleep apnea and stroke in a population of southern China

Abstract: Sleep habits are associated with stroke in western populations, but this relation has been rarely investigated in China. Moreover, the differences among stroke subtypes remain unclear. This study aimed to explore the associations of total stroke, including ischemic and hemorrhagic type, with sleep habits of a population in southern China. We performed a case-control study in patients admitted to the hospital with first stroke and community control subjects. A total of 333 patients (n = 223, 67.0%, with ischemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Another US study of over 55,000 adults also showed that in addition to CVD, the risks of hypertension and diabetes were also elevated among people with either short or long sleep duration [2] , [15] . The findings of the present study were broadly consistent with previous cross-sectional studies conducted in Chinese adults [4] [16] and with prospective studies [14] .…”
Section: Discussionsupporting
confidence: 92%
“…Another US study of over 55,000 adults also showed that in addition to CVD, the risks of hypertension and diabetes were also elevated among people with either short or long sleep duration [2] , [15] . The findings of the present study were broadly consistent with previous cross-sectional studies conducted in Chinese adults [4] [16] and with prospective studies [14] .…”
Section: Discussionsupporting
confidence: 92%
“…Second, daytime napping was positively associated with inflammatory markers, including serum C reactive protein [ 33 ], which might enhance the development of diabetes [ 34 , 35 ]. Third, daytime napping was an indicator of obstructive sleep apnea (OSA) [ 36 ]. OSA is characterized by the recurrent collapse of respiratory structures [ 37 ], which could increase sympathetic nervous activity and oxidative stress, and eventually cause insulin resistance [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms underlying the association between long sleep duration and elevated hsCRP and SUA are more speculative. First, a long sleep duration could be the result an undiagnosed illness or comorbidities that cause fatigue and lethargy [39]. Chronic inflammation is known to be involved in the main pathophysiology of many chronic diseases [40].…”
Section: Discussionmentioning
confidence: 99%